2015
DOI: 10.1242/jeb.129759
|View full text |Cite
|
Sign up to set email alerts
|

The water channel aquaporin-1a1 facilitates movement of CO2 and ammonia in zebrafish (Danio rerio) larvae

Abstract: The present study tested the hypothesis that zebrafish (Danio rerio) aquaporin-1a1 (AQP1a1) serves as a multi-functional channel for the transfer of the small gaseous molecules, CO 2 and ammonia, as well as water, across biological membranes. Zebrafish embryos were microinjected with a translation-blocking morpholino oligonucleotide targeted to AQP1a1. Knockdown of AQP1a1 significantly reduced rates of CO 2 and ammonia excretion, as well as water fluxes, in larvae at 4 days post fertilization (dpf ). Because A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…In the present study, the increase in mRNA expression level of AQP suggests that AQP serves as a NH 3 channel, synergized with Rh protein to facilitate ammonia excretion. A similar report appeared for zebrafish Danio rerio, where exposure to high external ammonia resulted in significantly higher AQP1a1 mRNA and protein abundance in Rhcg1-knockdown larvae (Talbot et al, 2015). Theoretical considerations argued that NH 4 + in the hemolymph may substitute for K + via a K + channel and NKA, and transport NH 4 + across the basolateral membrane into the epithelial cells (Choe et al, 2000;Wood et al, 2013).…”
Section: Evidence Of Rh Protein Associated With Ammonia Metabolism Mementioning
confidence: 56%
“…In the present study, the increase in mRNA expression level of AQP suggests that AQP serves as a NH 3 channel, synergized with Rh protein to facilitate ammonia excretion. A similar report appeared for zebrafish Danio rerio, where exposure to high external ammonia resulted in significantly higher AQP1a1 mRNA and protein abundance in Rhcg1-knockdown larvae (Talbot et al, 2015). Theoretical considerations argued that NH 4 + in the hemolymph may substitute for K + via a K + channel and NKA, and transport NH 4 + across the basolateral membrane into the epithelial cells (Choe et al, 2000;Wood et al, 2013).…”
Section: Evidence Of Rh Protein Associated With Ammonia Metabolism Mementioning
confidence: 56%
“…CO 2 crosses biological membranes by diffusion either through the lipid bilayer or through pores. A subset of aquaporins and related proteins [ 15 , 16 ] can behave as CO 2 channels [ 17 ]. Models based on artificial lipid bilayers indicated that the resistance for CO 2 diffusion is small and mostly limited by unstirred layers.…”
Section: Bicarbonate Transportmentioning
confidence: 99%
“…Plant aquaporin-mediated CO 2 transport has been implicated in several plant functions and importantly in plant growth [ 49 , 54 , 55 , 56 ]. Similarly, Perry and Gilmour and colleagues [ 52 , 53 ] have shown that the central function of the gills of zebrafish, or skin in larvae, to excrete ammonia and CO 2 is greatly supported by CO 2 /NH 3 channels.…”
Section: Physiological Role Of Co 2 Channels Inmentioning
confidence: 98%
“…The conclusion was that the Rh proteins are channels for both CO 2 and NH 3 , which agrees with the competition between CO 2 and NH 3 , as demonstrated by Endeward et al [ 6 ] for RhAG of the human red cell membrane. Later, the same group [ 53 ] showed that the zebrafish aquaporin-1a1 exhibits an analogous dual role as gas channel for both CO 2 and NH 3 . Morpholino knockdown of AQP-1a1 protein expression in zebrafish larvae, while not affecting oxygen uptake of the larvae, reduced their CO 2 release as well as their ammonia efflux, in addition to reducing their exchange of water.…”
Section: Evidence For Protein Co 2 Channelsmentioning
confidence: 99%
See 1 more Smart Citation